The Effective peer educators and counselors in adolescent efforts to quit smoking - Dais, Exsos Grend; Sutini, Titin; Purwati, Nyimas Heni; Srisantyorini, Triana (Jurnal Keperawatan, 2024)
Introduction: Adolescents face significant challenges in smoking cessation due to a lack of knowledge and low motivation in accessing information, methods, and management of quitting smoking. In this context, the role of peer educators and counselors, who are part of the adolescents' immediate environment, is crucial as it greatly influences their knowledge and attitudes toward quitting smoking. Objectives: This study aims to determine the effect of peer educators and counselors on adolescents' knowledge and attitudes towards smoking cessation. Methods: A quantitative pre-experimental design was employed using a one-group pre-test post-test approach. The research was conducted at a boarding school in Jambi, with a total sampling technique involving 89 male adolescent smokers aged 15-18 years. Bivariate analysis was performed using the non-parametric Wilcoxon Signed Rank Test with a significance level of 5% (0.05), and multivariate analysis was conducted using ordinal regression to assess the influence of confounding factors (age, economic status, psychological state, peers, and family) on adolescents' knowledge and attitudes towards smoking cessation. Results: The results indicated significant differences in adolescents' knowledge and attitudes towards smoking cessation before and after the intervention, with a p-value of 0.000 (p < 0.05). The confounding factors of age, economic status, and family had the most significant influence on adolescents' knowledge, while age, economic status, and peers had the most significant influence on adolescents' attitudes towards smoking cessation. Conclusions: Peer educators and counselors are effective in supporting adolescent efforts to quit smoking. As role models and health advocates, they help adolescents shift their focus away from smoking and increase their curiosity about smoking cessation through continuous counseling and the Upaya Berhenti Merokok (UBM) program, utilizing information media to enhance adolescent knowledge.